(untitled) (American Journal of Technology and Applied Sciences, 2023)
The main process of information exchange in the current society one of the directions is the informatization of education. Informatization of education is education in the broadest sense methodology in the field, psychological new information technologies aimed at pedagogical practice practice of effective use and creation (processing) of is considered as providing ti. In addition, information basis for the development of distance learning system serves as educational system in the process of information widely use of new information technology tools connection is made.